Voltage gain improvement of the operational transconductance amplifier designed with silicon-on-insulator fin field effect transistor after being exposed to proton-irradiation - De Sousa, Bruna Ramos; De Moraes Nogueira, Alexandro; Der Agopian, Paula Ghedini [UNESP]; Martino, Joao Antonio (IOP Publishing, 2021)
In this work, the influence of proton-irradiation in the voltage gain of two-stage operational transconductance amplifier (OTA) designed with silicon-on-insulator (SOI) fin field effect transistors (FinFETs) is studied. The OTA simulations were performed using Verilog-A approach based on experimental data extracted from the SOI FinFET electrical characterization, before and after proton-irradiation. The OTA is designed with SOI FinFETs of fin widths (Wfin) of 20 nm, 120 nm, and 870 nm, all in the same predefined inversion region (gm/ID = 8 V-1). All evaluated OTA circuits exposed to proton-irradiation presented a voltage gain increase (compared with pre-irradiation circuits), of 0.87 dB, 1.19 dB, and 6.16 dB for fin widths of 20 nm, 120 nm, and 870 nm, respectively. The results show that despite the typical radiation effect of degradation of the individual transistors (it being more severe for larger fin width SOI FinFET), these effects combined in OTA circuits result in an unexpected improvement in DC voltage gain, especially for wider fins. Focusing on the fin width impact on the OTA voltage gain, before and after proton-irradiation, it is much greater for narrow fin width SOI FinFET thanks to the better Early voltage.
Keywords: Fin field effect transistor; Operational transconductance amplifier; Proton-irradiation; Verilog-A